Coexistence and conflict in the family (Journal of Parents and Teachers, 2023)
The family life usually is followed by all kinds of conflicts because of being a social relationship. Friction leads to problems arising, and it's a point that we should take advantage of to build and learn from each other, but certain skills are necessary to deal with everything.
Keywords: family; conflict; resolve